“DAHSAT” (Dapur Sehat Atasi Stunting) sebagai Model Intervensi dalam Program Percepatan Penurunan Stunting - Kurniati Devi Purnamasari; Widya Maya Ningrum; Siti Rohimah (Jurnal SOLMA, 2023)
Background: Establishing the Dapur Sehat Atasi Stunting (DAHSAT) model as a program to accelerate stunting reduction by empowering cadres, midwives, and local community leaders. DAHSAT is a program designed to reduce stunting through team building, focusing on developing a balanced food menu for toddlers 0-59 months. It is hoped that the existence of DAHSAT can lessen the prevalence of stunting in toddlers based on empowering the local community to process menus and serve food with balanced nutritional content. Method: Implemented in Janggala Village, Cidolog District, by a team from the Faculty of Health Sciences, Galuh University. It will be held in three months, namely January-March 2023, using public education methods. Conduct focus group discussions (FGDs) with the target of relevant stakeholders (heads of Puskesmas, Midwives, nutrition departments, and cadres and training cadres in processing food ingredients that can be consumed by target families and educating stunting target families on how to process food ingredients that can utilize local foodstuffs. Results: The formation of a DAHSAT team and empowerment-based community education with a team of trained cadre mobilizers. Cidolog District's people are enthusiastic to participate in a series of activities initiated by the community service team. Conclusion: Cadre training and education activities for the community can be an alternative to supporting government programs in reducing stunting in the Janggala Village area, Cidolog District, which also involves targets.